1991
DOI: 10.1029/90ja02183
|View full text |Cite
|
Sign up to set email alerts
|

Local characterization of homogeneous turbulence in a space plasma from simultaneous Measurements of field components at several points in space

Abstract: The best method was sought for defining locally an electrostatic or an electromagnetic turbulence in a space plasma, based on the simultaneous measurement of several wave field components at several points in space. The turbulent field is supposed to be stationary in time and homogeneous in space. An estimate of a local field energy distribution, denoted F(ω,k), which specifies how the field energy observed by a limited number of satellites is distributed with regard to the angular frequency ω and to the wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
137
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 14 publications
1
137
0
Order By: Relevance
“…Pillai (1989) proved the wave telescope to be a generalized minimum variance technique. Pinçon and Lefeuvre (1991) expanded the method to include multidimensional (vectorial) observables and Motschmann et al (1996) further developed it in order to apply it to multipoint satellite measurements (e.g. Glassmeier et al, 2001;Narita et al, 2003;Constantinescu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Pillai (1989) proved the wave telescope to be a generalized minimum variance technique. Pinçon and Lefeuvre (1991) expanded the method to include multidimensional (vectorial) observables and Motschmann et al (1996) further developed it in order to apply it to multipoint satellite measurements (e.g. Glassmeier et al, 2001;Narita et al, 2003;Constantinescu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This, of course, is possible, providing one uses well adapted tools that take full advantage of the 3-D Cluster data. The k-filtering technique, which was introduced in the context of space physics by Pinçon and Lefeuvre (1991), was applied by Sahraoui et al (2003) to study the magnetic fluctuations measured by the Cluster-STAFF experiment. In this first application of the k-filtering technique to STAFF data, they have discussed the new opportunities that it offers to study the space plasma turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…We use a more robust method, namely, the k-filtering technique, to study the properties of low-frequency waves observed by the Cluster spacecraft and compare them to the results of Chaston et al [2009]. The k-filtering technique is a generalized minimum variance technique introduced into space science by Pinçon and Lefeuvre [1991]. This technique allows one to estimate the magnetic wave field energy distribution P(w, k) in the frequency and wave vector domain from data measured simultaneously at several points in space, under the assumption of (sufficient) stationarity of the time series (more details on this technique are given by Pinçon and Lefeuvre [1991], Pinçon and Motschmann [1998], Sahraoui et al [2003Sahraoui et al [ , 2010 [Balogh et al, 1997], and the Electric Fields and Waves (EFW) instrument provides 25 Hz electric field data [Gustafson et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…The k-filtering technique is a generalized minimum variance technique introduced into space science by Pinçon and Lefeuvre [1991]. This technique allows one to estimate the magnetic wave field energy distribution P(w, k) in the frequency and wave vector domain from data measured simultaneously at several points in space, under the assumption of (sufficient) stationarity of the time series (more details on this technique are given by Pinçon and Lefeuvre [1991], Pinçon and Motschmann [1998], Sahraoui et al [2003Sahraoui et al [ , 2010 [Balogh et al, 1997], and the Electric Fields and Waves (EFW) instrument provides 25 Hz electric field data [Gustafson et al, 1997]. Plasma data on ions and electrons (with 4 s resolution) were obtained from the Cluster Ion Spectrometry (CIS) and plasma electron and current experiment (PEACE) instruments, respectively [Rème et al, 2001;Johnstone et al, 1997].…”
Section: Introductionmentioning
confidence: 99%